Linguistic Markers of Grandiose Narcissism: A LIWC Analysis of 15 Samples. (October 2019) - Holtzman, Nicholas S.; Tackman, Allison M.; Carey, Angela L.; Brucks, Melanie S.; Küfner, Albrecht C. P.; Deters, Fenne Große; Back, Mitja D.; Donnellan, M. Brent; Pennebaker, James W.; Sherman, Ryne A.; Mehl, Matthias R.
Narcissism is unrelated to using first-person singular pronouns. Whether narcissism is linked to other language use remains unclear. We aimed to identify linguistic markers of narcissism. We applied the Linguistic Inquiry and Word Count to texts ( k = 15; N = 4, 941). The strongest positive correlates were using words related to sports, second-person pronouns, and swear words. The strongest negative correlates were using anxiety/fear words, tentative words, and words related to sensory/perceptual processes. Effects were small (each | r | < .10).